A Picture Performance Scale for the Hearing Impaired Individuals - Lalitha (Journal of All India Institute of Speech and Hearing, 1970)
Intelligence is defined by many people in different ways. Wechsler defines intelligence as the aggregate or global capacity of the individual to act purpose fully, to think rationally and to deal effectively with his environment. Intelligence can be measured by using  verbal and/or performance scales. Performance scale is one in which language is used only in the instructions, or not at all when directions are given in pantomime. The main characteristics of the performance test is that a response to, or a solution of, the task does not require the use of language. These tests have proved most valuable when used with persons handicapped  by language  disabilities, such as the deaf,  the foreign language speakers, the illiterate, and those who have speech or reading disabilities.